2011
DOI: 10.1097/aog.0b013e3182118ac3
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment of Heavy Menstrual Bleeding With Estradiol Valerate and Dienogest

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 23 publications
0
57
1
7
Order By: Relevance
“…Blood loss has been reported to be reduced by almost 90% in users of E2/dienogest Jensen et al 2011] and the use has a consistent positive impact on work productivity and activities of daily living in women with HMB [Wasiak et al 2012]. COC use also has a significant impact on the occurrence and severity of dysmenorrhea [Milsom et al 1990;Harada et al 2008].…”
Section: Menstrual Blood Lossmentioning
confidence: 99%
“…Blood loss has been reported to be reduced by almost 90% in users of E2/dienogest Jensen et al 2011] and the use has a consistent positive impact on work productivity and activities of daily living in women with HMB [Wasiak et al 2012]. COC use also has a significant impact on the occurrence and severity of dysmenorrhea [Milsom et al 1990;Harada et al 2008].…”
Section: Menstrual Blood Lossmentioning
confidence: 99%
“…45 Randomized trials involving women with heavy menstrual bleeding have shown the efficacy of an oral contraceptive containing estradiol valerate and dienogest, and of a combined contraceptive vaginal ring in treating this condition. 46,47 …”
Section: Heavy Menstrual Bleedingmentioning
confidence: 99%
“…Recently, two randomized trials of an OC containing estradiol valerate and dienogest provided solid proof of the efficacy of COCs for this treatment. 52,53 The reduction of blood loss in the study group varied from 60% to 70% compared with the placebo group. 52,53 Less-frequent menses or amenorrhea can be achieved with extended estrogen-progestogen COC regimens; however, there are no studies to prove that this mode of administration is superior to the cyclic use of COCs for treating heavy menstrual bleeding.…”
Section: Noncontraceptive Therapeutic Indications For Cocs Heavy Mensmentioning
confidence: 99%